東醫寶鑑 해독 처방에 대한 형상의학적 고찰 - 김종원(Jong Won Kim); 전수형(Soo Hyung Jeon); 정흥식(Heung Sik Jung); 강경화(Kyung Hwa Kang); 이인선(In Sun Lee); 이상훈(Sang Hoon Lee); 김규곤(Kyu Kon Kim); 이용태(Yong Tae Lee) (동의생리병리학회지, 2009)
Ji-San, the founder of HyungSang medicine, emphasized food intake and detoxification by stating, "Korean medicine begins with detoxification." Toxin accumulates in one's body unless the internal and external conditions stay in their harmony. The accumulation of toxin is also caused by western medication or one-sided diet, and detoxification should be considered in those cases. HwangRyunHaeDok-Tang reduces fire and heat, and the lesion is likely to locate in the upper body. BangPoongTongSung-San can be used for systemic disease. IkWoon-San also reduces fire and heat but mainly focuses on promoting urination. InSamPaeDok-San has an effect of curing the external symptoms of SangHan(傷寒), in addition to detoxification. SeoGakJiHwang-Tang, SoDok-Eum, and SeoGakSoDok-Eum can resolve the heat-toxin when it is located on the surface. SibJeonDaeBo-Tang enhances the detoxifying function of human body. GhamDu-Tang and JaGeum-Jung have a general effect on detoxification. KCI Citation Count: 0